Neurofeedback self-regulating training in patients with Post traumatic stress disorder: A randomized controlled trial study protocol - Jungtae Leem; Moon Joo Cheong; Sang-hoon Yoon; Hyunho Kim; Hee-Geun Jo; Hyeryun Lee; Jeesu Kim; Hyang Yi Kim; Geun-Woo Kim; Hyung Won Kang (Integrative Medicine Research, 2020)
Background: Post-traumatic stress disorder (PTSD) has become an important public health problem. However, the conventional therapeutic strategy, including pharmacotherapy and cognitive behavioral therapy, has limitations. Neurofeedback is a technique that utilizes electroencephalography (EEG) signaling to monitor human physiological functions and is widely used to treat patients with PTSD. The purpose of our study is to assess the efficacy and safety level of neurofeedback treatment in patients with PTSD using quantitative EEG. Methods: This is a randomized, waitlist-controlled, assessor-blinded, clinical trial. Forty-six patients with PTSD will be randomly assigned at a 1:1 ratio into two groups. The participants in the treatment group will receive neurofeedback treatment for 50 min, twice a week, for 8 weeks (16 sessions). Quantitative EEG will be utilized to monitor the physiological functions and brain waves of the participants. A four-week follow-up period is planned. The participants in the control group will wait for 12 weeks. The primary outcome is the Korean version of PTSD Checklist-5 (PCL-5-K) score. The PCL-5-K scores on week 8 will be compared between the two groups. Anxiety, depression, insomnia, emotions, EEG, quality-of-life, and safety level will be assessed as secondary outcomes. Discussion: This trial will describe a clinical research methodology for neurofeedback in patients with PTSD. The numerous subjective and objective secondary outcomes add to the value of this trial’s results. It will also suggest a therapeutic strategy for utilizing quantitative EEG in patients with PTSD. Our trial will provide basic evidence for the management of PTSD via an integrative treatment. Trial registration: Clinical Research Information Service (CRIS): KCT0003271.